Optical properties of chromium-doped fluoroindate glasses - Mendonça, C. R.; Costa, B. J.; Messaddeq, Y. [UNESP]; Zilio, S. C. (American Physical Society (APS), 1997)
This work reports on the optical properties of Cr3+ ions in the pseudoternary system InF3-GdF3-GaF3. Linear properties, investigated through absorption and emission spectra, provide information on the crystal field, the frequency, and number of phonons emitted during the absorption to the 4T2 band and the emission to the 4A2 ground state, and the Fano antiresonance line shape in the vicinity of the 4A2→2E transition. A study of the nonlinear refractive index as a function of the wavelength, carried out with the Z-scan technique, provides spectroscopic data about electronic transitions starting from the excited state.